EcXyl43 β-xylosidase: molecular modeling, activity on natural and artificial substrates, and synergism with endoxylanases for lignocellulose deconstruction - Ontañon, Ornella Mailén (2018)
Biomass hydrolysis constitutes a bottleneck for the biotransformation of lignocellulosic residues into bioethanol and high-value products. The efficient deconstruction of polysaccharides to fermentable sugars requires multiple enzymes acting concertedly. GH43 β-xylosidases are among the most interesting enzymes involved in hemicellulose deconstruction into xylose. In this work, the structural and functional properties of β-xylosidase EcXyl43 from Enterobacter sp. were thoroughly characterized. Molecular modeling suggested a 3D structure formed by a conserved N-terminal catalytic domain linked to an ancillary C-terminal domain. Both domains resulted essential for enzymatic activity, and the role of critical residues, from the catalytic and the ancillary modules, was confirmed by mutagenesis. EcXyl43 presented β-xylosidase activity towards natural and artificial substrates while arabinofuranosidase activity was only detected on nitrophenyl α-L-arabinofuranoside (pNPA). It hydrolyzed xylobiose and purified xylooligosaccharides (XOS), up to degree of polymerization 6, with higher activity towards longer XOS. Low levels of activity on commercial xylan were also observed, mainly on the soluble fraction. The addition of EcXyl43 to GH10 and GH11 endoxylanases increased the release of xylose from xylan and pre-treated wheat straw. Additionally, EcXyl43 exhibited high efficiency and thermal stability under its optimal conditions (40 °C, pH 6.5), with a half-life of 58 h. Therefore, this enzyme could be a suitable additive for hemicellulases in long-term hydrolysis reactions. Because of its moderate inhibition by monomeric sugars but its high inhibition by ethanol, EcXyl43 could be particularly more useful in separate hydrolysis and fermentation (SHF) than in simultaneous saccharification and co-fermentation (SSCF) or consolidated bioprocessing (CBP).